Nocturnal enuresis in an adolescent with anxiety disorder during the COVID-19 pandemic. - Huete-Cordova, Maria A. (2022)
The case of an adolescent with nocturnal enuresis since childhood, and anxiety symptoms during adolescence, associated with psychosocial factors and family dynamics, is presented. During the COVID-19 pandemic, he presented intense symptoms of anxiety related to fears of dying and/or experiencing a serious illness, reasoned for which he was taken to the emergency room on several occasions. The patient responded favorably to antidepressant medications, and individual and family psychotherapy approaches. Nocturnal enuresis es an elimination disorder rarely seen in adolescence, and whose diagnosis and treatment are important due to its impact on the patient’s psychosocial functioning and greater probabilities of comorbidity. The effects of the COVID-19 pandemic on adolescents and its higher risk of presenting anxiety, depression and stress associated with enuresis, are also discussed.